ETIKA PENGUSAHA MUSLIM KOTA MALANG (Studi Kasus pada Bubur Ayam Abah Odil dan Rental Mobil TW) - Heksi Rian Adha (Jurnal Ilmiah Mahasiswa FEB, 2014)
This article was made to find out how important the use of ethics in business and everyday life by employers, especially Muslim businessmen on the importance of ethics in business, motivation of entrepreneurs to act ethically in business, and the ethical ideal (conventional or Islamic). There is a paradigm that if honest in business, the business will be in trouble, and God did not participate in the business. But entrepreneurs in doing business refers to God through the Qur'an and the Prophet Muhammad then be able to apply the ethics of wages or salaries, working comfort, and implement a business ethics Muslim entrepreneurs with both the employees and its customers. So that business activities are conducted by Muslim businessmen in accordance with Islamic business ethics.   Keyword: business ethics, Muslim bisunessmen, employers, customers, Islamic business ethics